1982
DOI: 10.1111/j.1365-2133.1982.tb00521.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased factor VIII-related antigen in necrobiosis lipoidica and widespread granuloma annulare without associated diabetes

Abstract: Factor Vlll-related antigen was found to be raised in diabetics, and in patients with necrobiosis lipoidica and widespread granuloma annulare who were not diabetic. It was not increased in patients with solitary lesions of granuloma annulare.The relationship of factor Vlll-related antigen to the development of micro-angiopathy in these conditions is discussed.Factor VIII is a complex of two plasma glycoproteins which are of vital importance in blood coagulation and haemostasis. It comprises factor VIII procoag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…They both have the same type of subunit structure (Mosher, 1980), are present in plasma, secreted by endothelial cells and absorbed by collagen (Legrand et al, 1978). These similarities together with the observation that fibronectin (reported here) and factor VIII related antigen are raised in diabetes, NL and generalized GA (Majewski et al, 1982) suggest that these two factors might contribute to the thickening of blood vessels.…”
Section: Discussionsupporting
confidence: 83%
“…They both have the same type of subunit structure (Mosher, 1980), are present in plasma, secreted by endothelial cells and absorbed by collagen (Legrand et al, 1978). These similarities together with the observation that fibronectin (reported here) and factor VIII related antigen are raised in diabetes, NL and generalized GA (Majewski et al, 1982) suggest that these two factors might contribute to the thickening of blood vessels.…”
Section: Discussionsupporting
confidence: 83%
“…Diabetes was present in 10 of 14 patients studied which supports the earlier findings of diabetes in about two thirds of the patients with NL [1], NL and granuloma annulare have been reported together in the same patient [10], Furthermore, it has been recently reported that patients suffering from NL as well as granuloma annulare and sarcoidosis have a deficiency in granulocyte functions [11], al though normal functions have been reported in another study [12]. This possible impair ment of granulocyte function as well as a finding of factor-VIlI-rclated antigen in the affected skin area of NL [13] in association with local trauma may lead to development of NL. Hypothetically, local trauma in the skin could induce precipitation of factor VIII [13], and impaired granulocyte function in diabetes [11,14] could lead to an altered in flammatory and repair process, resulting in the development of LN.…”
Section: Discussionmentioning
confidence: 83%
“…This possible impair ment of granulocyte function as well as a finding of factor-VIlI-rclated antigen in the affected skin area of NL [13] in association with local trauma may lead to development of NL. Hypothetically, local trauma in the skin could induce precipitation of factor VIII [13], and impaired granulocyte function in diabetes [11,14] could lead to an altered in flammatory and repair process, resulting in the development of LN. Immune complexes may play a role in the pathogenesis of NL only occasionally or in a limited group of diabetes mellitus patients [15],…”
Section: Discussionmentioning
confidence: 99%
“…Severe NL lesions usually demonstrate vascular occlusion and endothelial cell proliferation 7 . Increased factor VIII production has been reported to cause platelet adhesion in NL patients 23 . The expression of Glut‐1 receptors by fibroblasts in NL lesions is indicative of defective glucose transport mechanisms which play a role in the physiology of this disease 11 .…”
Section: Discussionmentioning
confidence: 99%
“…7 Increased factor VIII production has been reported to cause platelet adhesion in NL patients. 23 The expression of Glut-1 receptors by fibroblasts in NL lesions is indicative of defective glucose transport mechanisms which play a role in the physiology of this disease. 11 Taken together, it is reasonable to hypothesize that diabetic metabolic changes may be one of the key elements involved in the pathophysiology of NL lesions.…”
Section: Discussionmentioning
confidence: 99%